2014
DOI: 10.1080/00028487.2014.952449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Forest Road Culverts and Waterfalls on the Fine‐Scale Distribution of Brook Trout Genetic Diversity in a Boreal Watershed

Abstract: Habitat fragmentation has become an increasing concern in conservation biology and is of prime importance with the expansion of forest road networks toward boreal and arctic regions. The aim of this study was to evaluate the effects of artificial and natural barriers to fish movement on the fine‐scale distribution of genetic diversity in Brook Trout Salvelinus fontinalis. We genotyped 995 individuals sampled from 25 locations in a boreal watershed fragmented by culverts and natural waterfalls. Using a landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 107 publications
4
59
1
Order By: Relevance
“…Nathan et al () found that in Connecticut, Brook Trout populations located upstream of road culverts displayed lower diversity values ( A R : 2.74–4.85, H e : 0.464–0.775, based on 17 populations) than populations unaffected by culverts ( A R : 3.10–4.62, H e : 0.625–0.761, based on 11 populations). Torterotot et al () also described reduced genetic diversity in Brook Trout populations located upstream of barriers. In general, our study found that Brook Trout populations with a high degree of connectivity and wild–wild admixture tended to also exhibit higher levels of genetic variation than populations where little to no admixture was detected.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nathan et al () found that in Connecticut, Brook Trout populations located upstream of road culverts displayed lower diversity values ( A R : 2.74–4.85, H e : 0.464–0.775, based on 17 populations) than populations unaffected by culverts ( A R : 3.10–4.62, H e : 0.625–0.761, based on 11 populations). Torterotot et al () also described reduced genetic diversity in Brook Trout populations located upstream of barriers. In general, our study found that Brook Trout populations with a high degree of connectivity and wild–wild admixture tended to also exhibit higher levels of genetic variation than populations where little to no admixture was detected.…”
Section: Discussionmentioning
confidence: 95%
“…With the increased fragmentation of Brook Trout populations due to habitat alterations (Timm et al, ; Torterotot et al, ; Whiteley et al, ), extirpation of nearby populations (Letcher et al, ), and thermal barriers associated with increased temperatures (Aunins et al, ), population monitoring is essential to minimize the rate of species decline. Incorporating genetic tools into population assessments can reveal previously unrecognized barriers to dispersal and identify population‐level relationships that can help inform management delineations and translocation decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), brook trout (Torterotot et al . ), three‐spined stickleback ( Gasterosteus aculeatus L.) (Raeymaekers et al . ) and Cottus gobio (Hänfling & Weetman ).…”
Section: Discussionmentioning
confidence: 99%
“…; Torterotot et al . ). In line with this, a review of effectiveness of habitat rehabilitation techniques ranked the connection of isolated habitats by improving passage among the most successful ones (Roni et al .…”
Section: Introductionmentioning
confidence: 97%